Age-associated accumulation of carbamylation-derived products in tissues is independent from the myeloperoxidase pathway in mice - Christine Pietrement; Anaïs Okwieka; Lucile Cadoret; Manon Doué; Philippe Gillery; Stéphane Jaisson (PLoS ONE, 2026)
Carbamylation is a nonenzymatic post-translational modification that alters protein structural and functional properties and is involved in the pathogenesis of many diseases. It results from isocyanic acid binding to protein amino groups, generating carbamylation-derived products, including homocitrulline (HCit) when the reaction targets the ε-amino group of lysine residues. Isocyanic acid is produced by two major sources in vivo , the spontaneous dissociation of urea and the myeloperoxidase (MPO)-catalyzed conversion of thiocyanate, but their respective contribution to carbamylation is disputed in literature. Here, we compared tissue accumulation of HCit in wild-type versus MPO-deficient mice during ageing. Our results showed that the kinetics and amplitude of carbamylation were not reduced in MPO-deficient mice. Furthermore, carbamylation was intriguingly enhanced in younger MPO-deficient mice, suggesting the presence of compensatory mechanisms. These findings suggest that the MPO pathway is not necessarily required for age-associated systemic carbamylation.